Development of Contextual Environmental Issues-Based Ecology E-Books to Improve Students' Critical Thinking Skills - Fajrul Falah; Ilidio Ximenes Moreira; Noer Af'idah; Andri Wahyu Wijayadi; Roudhoutul Aulia Rochim (Journal of Natural Science and Integration, 2026)
This research aims to develop a valid and effective contextual environmental issue-based ecology e-book to improve students' critical thinking skills. This research uses a Research and Development (R&D) approach with a 4D (Define, Design, Develop, Disseminate) model. The research population consists of junior high school students, and the test subjects (as the unit of analysis) comprise 61 grade VII students from two classes. This sample size was selected to ensure data representativeness and to more comprehensively measure the effectiveness of the media. Data collection techniques include validation sheets by subject matter experts, media experts, and science teachers, as well as pretest and posttest instruments based on critical thinking indicators. Data were analyzed using descriptive statistics, N-Gain analysis, and classical learning mastery percentage. The validation results showed an average score of 3.70, indicating high feasibility. The effectiveness test results showed an increase in the average score from 55 to 75, with an N-Gain of 0.44 (medium), and an increase in classical learning mastery from 31% to 85%. This study offers novelty by systematically mapping six critical thinking indicators into the interactive features of the e-book that specifically address local environmental issues. Thus, the developed e-book is highly feasible and proven to be effective as an innovative independent teaching material in science learning. Keywords: ecology e-book, contextual environmental issues, critical thinking skills